1999
DOI: 10.1007/bf02918388
|View full text |Cite
|
Sign up to set email alerts
|

Gastric mucosal inflammatory responses toHelicobacter pylori lipopolysaccharide: Suppression of caspase-3 and nitric oxide synthase-2 by omeprazole and sucralfate

Abstract: Our findings implicate caspase-3 involvement in gastric mucosal inflammatory responses toH. pylori lipopolysaccharide, and point towards participation of NOS-2 in the amplification of the cell death-signaling cascade. We also show that anti-ulcer agents, omeprazole and sucralfate, are capable of suppressing the H. pylori-induced mucosal inflammatory responses by interfering with the events propagated by NOS-2 and caspase-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…PPAR γ suppresses the growth and invasion of human colon [71] and gastric [72, 73] and esophageal carcinoma cells [74], and both PPAR γ [75] and PPAR α have anti-inflammatory actions [76]. Thus, reduction of PPAR α and PPAR γ expression may be an additional mechanism for facilitating the proinflammatory and tumor-promoting effects of GW501516.…”
Section: Discussionmentioning
confidence: 99%
“…PPAR γ suppresses the growth and invasion of human colon [71] and gastric [72, 73] and esophageal carcinoma cells [74], and both PPAR γ [75] and PPAR α have anti-inflammatory actions [76]. Thus, reduction of PPAR α and PPAR γ expression may be an additional mechanism for facilitating the proinflammatory and tumor-promoting effects of GW501516.…”
Section: Discussionmentioning
confidence: 99%
“…An experimental study in rats found that IL-4 had a rapid increase after the 4th day of the ulcer onset and remained high throughout the entire period of healing. The authors also stated that sucralfate, by eliciting rapid induction in IL-4 expression, was capable of efficient suppression of the mucosal apoptotic events, the cessation of which determined the efficiency of the healing process [39]. In a study about cytokine expression in pediatric H. pylori infection, IL-4 was present in both H. pylori infected and uninfected cases.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric lesions can be also induced by necrotizing agents like acids, alkalies [16] and 80% ethanol [17,18]. Another model of gastritis can be induced by intragastric application of either H. pylori itself [19] or its lipopolysaccharides [20,21].…”
Section: Introductionmentioning
confidence: 99%